Computational aeroacoustic study of co-rotating rotors in hover - Grande, Edoardo; Shubham, Shubham; Avallone, Francesco; Ragni, Daniele; Casalino, Damiano (Elsevier, 2024)
This paper aims to investigate, by means of Lattice-Boltzmann simulations, the flow-field and far-field noise of two co-axial co-rotating rotors operating at 3000 rpm in hover conditions. The two co-rotating configurations are made by 2 × 2-bladed rotors with a fixed axial separation and two different azimuthal separations Δ𝜙 equal to 84◦ and 12◦. Isolated 2- and 4-bladed rotors, are also simulated at the same operating conditions and used as aerodynamic and aeroacoustic reference. For both Δ𝜙 = 84◦ and 12◦, the upper rotor tip vortices are accelerated downstream due to the induction from the lower rotor, avoiding blade vortex interaction (BVI). The lower rotor tip vortices convect into the wake with a lower velocity, causing BVI for Δ𝜙 = 12◦. The lower rotor shows a reduction of thrust, relative to the upper rotor, of 36% and 66% for Δ𝜙 = 84◦ and 12◦, respectively. For Δ𝜙 = 12◦, the lower blades act as a wing flap for the upper ones, increasing their thrust. The tonal noise emission for the co-rotating rotors is driven by the interference between the acoustic waves from upper and lower rotors. Because of destructive interference, the configuration Δ𝜙 = 84◦ shows a first harmonic up to 15 dB lower than Δ𝜙 = 12◦, but still 4.5 dB higher than the isolated 4-bladed rotor.
Keywords: Co-rotating rotors; Aeroacoustics; LBM; PowerFLOW